Black Students’ Experiences of Academic Support Programs during First Year at University: Case of Extended Studies - Belinda Ramathetse Matabane; Mogalatjane Edward Matabane (Research in Social Sciences and Technology, 2021)
In the last three decades, historically white, liberal arts universities began to admit small numbers of black students from rural communities because apartheid policies relaxed. However, those liberal arts universities had doubts about black students’ key skills and knowledge to cope with the demands of higher education. This situation gave birth to Extended Studies Program (ESP) whereby the traditional three-year degree program was extended by a year to close this gap. This study seeks to answer the question: What are black students’ experiences and views about academic support offered to them during their first year at university? In this study both qualitative and quantitative research methods were followed, and purposive sampling was deployed. Data were generated from different sources for triangulation, namely questionnaires and interviews. Participants (N=104) were made of 43 males and 61 females. The results of the study suggest that the need for academic support is not exclusive to first-year students. Improved systematic academic support gives rise to improved student academic performance. Throughout the study, necessity, and urgency of Academic Support Programs (ASPs) is recognized. Recommendations are made suggesting that ASPs be administered throughout the undergraduate programs and not just at the first-year level of study.